Implementasi Manajemen Berbasis Madrasah di Madrasah Aliyah Raudlatul Ulum Guyangan Pati - Abas, Moh. Ibnu; Nurkolis, Nurkolis; Kusumaningsih, Widya (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze the implementation of four pillars of Madrasah-Based Management (MBM)—autonomy, participation, transparency, and accountability—in the governance of MA Raudlatul Ulum Guyangan Pati. A qualitative descriptive approach was employed to explore the phenomenon within its natural context. Data were collected through in-depth interviews, observations, document analysis, and examination of institutional communication through official social media platforms. Informants included the principal, teachers, school committee members, and community representatives selected purposively based on their involvement in school management. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that MBM has been implemented through a collective governance model. Institutional autonomy operates through deliberative decision-making under the coordination of the foundation. Community participation emerges as a strong social capital supported by trust and long-standing cultural ties. Transparency is practiced through internal communication forums and public dissemination of activities via digital media, while accountability is reflected in program reporting and institutional documentation. The study reveals that the effectiveness of MBM is influenced not only by formal managerial systems but also by pesantren organizational culture emphasizing trust, collaboration, and moral responsibility. This research contributes to the conceptual development of culturally grounded and digitally adaptive MBM governance to support sustainable quality improvement in Islamic secondary education.